DO WE NEED REFORMS IN THE TERTIARY EDUCATION SYSTEM? - Piotr Dutkiewicz (Moscow Polytechnic University, 2016)
Globally, universities today face at least four sets of challenges. The first is to meet the expectation to prepare people for jobs available in today's globalized economy and to rethink yesterday's teaching practices. Secondly, it is necessary to create an educational system that prepares students to work in fields that do not exist today, therefore, further investment in teachers' skills should take place. Third, many scholars are pursuing their personal careers in an environment of high competition, so they are becoming politically and socially too "correct". Fourth, Universities have to undergo structural reforms that in the long term will limit broader access to higher education. Universities need to change and undergo a transition from: (1) teacher-centric to learning-centric education, (2) classroom-based teaching to anyplace, anytime learning, (3) mandated courses to hyper-individualized learning, (4) a general population of consumers to a growing population of producers.